Transformation Needed - Simone Westerfeld; Beatrix Wullschleger (Credit and Capital Markets – Kredit und Kapital, 2020)
For the sixth time, international academics and practitioners met for a successful credit risk conference. Keynote speeches and academic sessions highlighted current developments and necessary improvements in areas such as fintech, regulation, credit ratings and risk analysis. Digitization also leaves its mark in this area and requires, to varying degrees, a transformation of affected persons as well as applied systems or models.
Keywords: G210; G280; 330; Regulation; Bank Lending; Credit; Risk Assessment; Reserve Requirements